Determinasi Minat PrEP pada LSL: Studi pada Komunitas Daring Gay Indonesia (X Community Tab) - Alfi Septian Nurul Huda; Novie Elvinawaty Mauliku; Suhar Suhat; Dyan Kunthi Nugrahaeni; Yeni Mahwati (Malahayati Nursing Journal, 2026)
ABSTRACT HIV (Human Immunodeficiency Virus) is a virus that attacks the immune system and can be prevented through biomedical interventions such as Pre-Exposure Prophylaxis (PrEP), which involves the use of antiretroviral (ARV) medication by individuals who are not infected with HIV. PrEP has been shown to be highly effective in preventing HIV transmission, particularly among high-risk populations such as men who have sex with men (LSL). Despite its proven effectiveness, interest in PrEP use varies across individuals and communities, indicating the need to understand factors influencing PrEP uptake intention. This study aimed to examine the association between education level, sexual orientation, knowledge of PrEP, and multiple sexual partner behavior with interest in PrEP use among members of an Indonesian gay online community (X Community Tab). This study employed a cross-sectional design involving 376 participants who were members of the X Community Tab online community. Data were collected through an online questionnaire and analyzed using univariate, bivariate, and multivariate statistical approaches with IBM SPSS version 25. The variables examined included education level, sexual orientation, knowledge of PrEP, and multiple sexual partner behavior. The analysis revealed a significant association between knowledge of PrEP (p = 0.001) and multiple sexual partner behavior (p = 0.001) with interest in PrEP use. In contrast, no significant association was found between education level (p = 0.634) or sexual orientation (p = 0.974) and interest in PrEP use. Adequate knowledge of PrEP and engagement in multiple sexual partner behavior are associated with greater interest in PrEP use as an HIV prevention strategy. It is recommended that PrEP-related education be strengthened and more strategically targeted toward LSL populations, particularly through digital media platforms and healthcare services. Keywords: HIV, Men Who Have Sex With Men (LSL), Knowledge, Sexual Behavior, PrEP.  ABSTRAK HIV (Human Immunodeficiency Virus) merupakan virus yang menyerang sistem kekebalan tubuh dan dapat dicegah melalui pendekatan biomedis seperti Pre-Exposure Prophylaxis (PrEP), yaitu penggunaan obat antiretroviral (ARV) oleh individu yang belum terinfeksi HIV. PrEP terbukti efektif dalam mencegah penularan HIV, terutama pada kelompok berisiko tinggi seperti lelaki seks dengan lelaki (LSL). Meskipun efektivitasnya telah banyak dibuktikan, minat penggunaan PrEP masih bervariasi, sehingga penting untuk memahami faktor-faktor yang memengaruhi minat tersebut. Penelitian ini bertujuan untuk mengetahui hubungan antara tingkat pendidikan, orientasi seksual, pengetahuan tentang PrEP, dan perilaku seksual bergonta-ganti pasangan dengan minat penggunaan PrEP pada komunitas daring Gay Indonesia (X Community Tab). Penelitian ini menggunakan desain potong lintang (cross-sectional) dengan jumlah partisipan sebanyak 376 anggota komunitas daring X Community Tab. Data dikumpulkan melalui kuesioner daring dan dianalisis menggunakan pendekatan univariat, bivariat, dan multivariat dengan bantuan perangkat lunak IBM SPSS versi 25. Variabel yang diteliti meliputi tingkat pendidikan, orientasi seksual, pengetahuan tentang PrEP, dan perilaku seksual bergonta-ganti pasangan. Hasil analisis menunjukkan adanya hubungan yang signifikan antara pengetahuan tentang PrEP (p = 0.001) dan perilaku seksual bergonta-ganti pasangan (p = 0.001) dengan minat penggunaan PrEP. Namun, tidak ditemukan hubungan yang signifikan antara tingkat pendidikan (p = 0.634) maupun orientasi seksual (p = 0.974) dengan minat penggunaan PrEP. Pengetahuan yang baik tentang PrEP dan perilaku seksual bergonta-ganti pasangan berhubungan dengan meningkatnya minat penggunaan PrEP sebagai upaya pencegahan HIV. Oleh karena itu, disarankan agar edukasi mengenai PrEP ditingkatkan secara lebih terarah kepada kelompok LSL, khususnya melalui media digital dan layanan kesehatan. Kata Kunci: HIV, Lelaki Seks dengan Lelaki, Pengetahuan, Perilaku Seksual, Prep.